The Effects of Proximity and Empathy on Ethical Decision-Making: An Exploratory Investigation - Mencl, Jennifer; May, Douglas R. (2009)
The goals of this research were to (1) explore the direct effects of and interactions between magnitude of consequences and various types of proximity – social, psychological, and physical – on the ethical decision-making process and (2) investigate the influence of empathy on the ethical decision-making process. A carpal tunnel syndrome vignette and questionnaire were administered to a sample of human resource management professionals to test the hypothesized relationships. Significant relationships were found for the main effects between magnitude of consequences and principle-based evaluation, cognitive empathy and principle-based evaluation, and empathy and moral intention. Physical proximity moderated the relationships between magnitude of consequences and utilitarian evaluation as well as magnitude of consequences and moral intention. Cognitive empathy moderated the relationships between magnitude of consequences and principle-based evaluation and physical proximity and utilitarian evaluation. Affective empathy marginally moderated the relationship between physical proximity and principle-based evaluation. Future research directions, management implications, and strengths and weaknesses of the research are discussed.
Keywords: Proximity; Moral Intensity; moral evaluations; magnitude of consequences; ethical decision-making process; Empathy